2014
DOI: 10.1016/j.jcma.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological improvement after intravenous tissue plasminogen activator infusion in patients with ischemic stroke aged 80 years or older

Abstract: In older patients, thrombolytic treatment increased the rate of neurological improvement compared with patients not receiving the treatment. The study showed that thrombolytic treatment may be beneficial for patients ≥80 years, but should be performed with extreme care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…26 Also, in a study by Zeevi et al, 19 older patients treated with IV-rtPA presented with a 12-month modified Barthel Index score comparable to that of younger patients. Moreover, several studies revealed a similar rate of early neurological improvement in younger and older patients, 7,9 and higher rates of early neurological improvement 21 and improved functional outcome among elderly patients who underwent thrombolysis versus elderly patients who did not undergo thrombolysis. 8,25 In the present study, hemorrhagic transformation or mortality rates at day 90 were similar in older and younger patients.…”
Section: Article In Pressmentioning
confidence: 92%
See 1 more Smart Citation
“…26 Also, in a study by Zeevi et al, 19 older patients treated with IV-rtPA presented with a 12-month modified Barthel Index score comparable to that of younger patients. Moreover, several studies revealed a similar rate of early neurological improvement in younger and older patients, 7,9 and higher rates of early neurological improvement 21 and improved functional outcome among elderly patients who underwent thrombolysis versus elderly patients who did not undergo thrombolysis. 8,25 In the present study, hemorrhagic transformation or mortality rates at day 90 were similar in older and younger patients.…”
Section: Article In Pressmentioning
confidence: 92%
“…Most studies seem to show worse outcome and increased mortality in patients aged over 80 years old with acute ischemic stroke treated with IV-rtPA when compared with younger counterparts. [7][8][9][10][11][12][13][14][15][16][17] Nevertheless, patients from this age group still seem to benefit from this treatment and do not seem to have an increased risk of symptomatic intracranial hemorrhage after IV-rtPA, as demonstrated in several observational studies [7][8][9][11][12][13][14]16,[18][19][20][21][22][23][24][25] and also in a randomized controlled trial. 26 Thus, there is increasing evidence supporting the finding that old age, by itself, should not be a reason to exclude patients from treatment with IV-rtPA.…”
Section: Introductionmentioning
confidence: 97%
“…21 The patient's neurological condition was evaluated as described in our previous study. 3 Early neurological improvement (ENI) was defined as a decrease of more than 6 points (compared with baseline) or an improvement in the NIHSS of 0 or 1 within 24 hrs after tPA infusion. Neurological improvement (NI) was defined as a >6-point improvement (compared with baseline) or an improvement in the NIHSS of 0 or 1 at discharge.…”
Section: Methodsmentioning
confidence: 99%
“…1 From then on, most studies on thrombolytic therapy for ischemic stroke patients followed the guidelines for thrombolytic therapy for acute stroke, using intravenous tPA (0.9 mg/kg, maximum 90 mg), with a bolus of 10% of the total dose given within 1─2 mins, followed by an infusion lasting 60 mins. [2][3][4] Owing to a higher symptomatic hemorrhagic transformation rate (sHT) in patients who received standard-dose tPA therapy, [5][6][7] a lower dose of tPA for ischemic stroke patients was suggested. 8,9 Subsequently, the Japan Alteplase Clinical Trial (J-ACT) study reported that IV low-dose tPA (0.6 mg/kg) could offer both clinical efficacy and safety as a standard dose, 8 and the Japanese drug safety authority has approved the use of tPA 0.6 mg/kg for patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors defined improvement as the NIHSS score improvement by 40% from baseline and compared patients at 1 h after thrombolysis (very early neurological improvement -VENI) and at 24 h (early neurological improvement -ENI) [18]. Early neurological improvement was also defined as eight or more points in NIHSS 24 h after thrombolysis while neurological improvement was defined as an improvement of at least eight points at discharge (compared with baseline) [19].…”
Section: Introductionmentioning
confidence: 99%